Analisis Tingkat Ketercapaian Tugas Perkembangan Karier Mahasiswa dan Implikasinya Terhadap Pelayanan Konseling - Redi Eka Andriyanto; Ratna Widiastuti; Yusmansyah Yusmansyah (Indonesian Journal of Educational Counseling, 2017)
The aims this study for examine the achievement level of student's career in terms of Ginsberg's career theory, after that which will be pursued what counseling service can be used to help students complete the task of career development. The research approach that used is quantitative descript. The population of this research is FKIP UNILA students. In the determination of the research sample, researchers used random sampling of 91 students. Data were collected by Likert Scale, and analyzed with mean hypotetic. The results of this research indicate that (1) the level of achievement of the career of FKIP UNILA students are in medium category, and the level of achievement of the career development task is decreased from the fantasy-tentatif-realistic phase, (2) the implication of the level career achievement task of development FKIP UNILA student is in the medium category, and the level achievement of career development task is decreasing from the fantasy-tentatif-realistic phase. Implications toward counseling services. There is a continuous, planned, and needs-based career guidance program, career information services are held, career visits and future studies are held, while counselors have implications for the need to increased competence and professionalism.